The Uniqueness of Culture: Acculturation between Religion and Local Culture on Indonesian Sumenep Batik Motifs - Lulus Sugeng Triandika (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
Sumenep Batik has characteristics such as asymmetrical motifs and colors that reflect natural representations. Generally, figures of plants, animals, and acculturation inspire the creation of batik motifs. However, the inspiration for the motifs of the Sumenep Batik is strongly influenced by the acculturation between religious values and local culture. The pattern of motifs is considered a form of cultural communication with Sumenep Batik as the medium. This article aimed to discover the meaning of the motifs from the perspective of religion and local culture acculturation because studies on the motifs of Sumenep Batik still need to be made available. Economic and human resource aspects dominate Sumenep Batik's research. The method used is descriptive qualitative, collecting data through observation, literature review, and interviews with Madurese Batik artisans, entrepreneurs, and cultural observers. The summary of the information is then analyzed using Charles Sanders Peirce's semiotic theory. The result is that there has been a process of cultural acculturation -starting from the 13th century- as evidenced by the existence of five elements of cultural acculturation in the pattern of Sumenep Batik motifs. Starting from the influence of the Hindu-Buddhist kingdom, then the Islamic sultanate, the influence of Chinese culture, then the influence of coastal culture, and finally, the influence of religious elements that influence the motifs of Sumenep Batik. Based on the semiotic analysis, the pattern of batik motifs originating from plant parts influences the implementation of Islamic religiosity elements. In Islamic rules, it is forbidden to depict creatures that have souls. Besides that, the combination of plants and orange color also describes the warmth and happiness expected to always exist in the people of Sumenep Madura.